Sistem Pendukung Keputusan Pemilihan Tenaga Kontrak Pantarlih Menggunakan Metode PSI - Sitorus, Harry Polin (STMIK Budi Darma, 2024)
Decision Support System is an information system that is flexible, interactive, adaptable and developed to provide information, modeling and data manipulation so that it can produce various alternative decisions and answers in helping management deal with various problems. Meanwhile, Pantarlih is an officer formed by the Voting Committee (PPS) to update and register voter data. The difficulty in determining pantarli is that there is an election that is not transparent or not open, one of which is by showing directly and not based on certain criteria so that those selected as Pantarlih in Ujung Serdang village do not have good abilities. For this reason, a decision support system (SPK) is needed that can assist the committee in determining Pantarlih contract workers who are in accordance with the criteria needed.PSI method is a method for solving multicriteria decision making (MCDM). By using many criteria, a decision support system for pantarlih selection can be carried out at the tj.morawa sub-district election committee office. In addition, the results of the PSI method are based on ranking so as to determine who is selected to become Pantarlih contract workers based on ranking and the number of Pantarlih contract workers received.